2015
DOI: 10.4103/2153-3539.151921
|View full text |Cite
|
Sign up to set email alerts
|

A bayesian approach to laboratory utilization management

Abstract: Background:Laboratory utilization management describes a process designed to increase healthcare value by altering requests for laboratory services. A typical approach to monitor and prioritize interventions involves audits of laboratory orders against specific criteria, defined as rule-based laboratory utilization management. This approach has inherent limitations. First, rules are inflexible. They adapt poorly to the ambiguity of medical decision-making. Second, rules judge the context of a decision instead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Traditionally, to evaluate lab test utilization, metrics such as those described earlier (e.g., test ordering volumes and ordering rates) are commonly analyzed ( 24–26 ). Other metrics such as test positivity rate have also been described as a useful benchmark for examining lab test utilization ( 27–30 ). While research involving this metric is still evolving, low positivity rate has been suggested as a possible signal for test overutilization, while high positivity rate has been suggested as a possible signal for test underutilization ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, to evaluate lab test utilization, metrics such as those described earlier (e.g., test ordering volumes and ordering rates) are commonly analyzed ( 24–26 ). Other metrics such as test positivity rate have also been described as a useful benchmark for examining lab test utilization ( 27–30 ). While research involving this metric is still evolving, low positivity rate has been suggested as a possible signal for test overutilization, while high positivity rate has been suggested as a possible signal for test underutilization ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the graph is easy to understand. The method does not involve advanced mathematics (e.g., algebra, calculus) [24]. Second, although simple to understand, the graph can represent a complex process.…”
Section: Strengths Of Modeling Guideline Adherence As a Graphmentioning
confidence: 99%
“…Listing questions that, if answered, could narrow the differential diagnosis can be useful. Performance measures of diagnostic tests, contraindications for their use, and complication rates could be incorporated in their knowledge bases [ 44 ]. This information can be applied in the case of an individual patient to simulate a posttest probability given a prior probability and test result, such as using likelihood ratios [ 45 ].…”
Section: Next-generation Diagnosis Support Systemsmentioning
confidence: 99%